A Design and Fabrication of Installation Tables and Panel Kits Electric Power System 1 ɸ and 3 ɸ As Practicum Kits at the Power Electronics Laboratory: Panel Kits Electric Power System 1 ɸ and 3 ɸ - Irwansyah Syam; Lindawati Lindawati; Nuzuli Fitriadi (LPPM Politeknik Aceh Selatan, 2021)
An installation drawing is an image that plays a very vital and decisive role in an electrical installation design, because only with the help of a drawing an electrical installation project can be carried out. So to increase students' knowledge and skills about electrical systems, it is necessary to develop an electric power system installation kit. Electric power system installation kits are a device in the form of an electric circuit that produces an electric current, it can be a lamp or a source of electrical energy from generators and electric machines. The purpose of this research is to design drawings and fabrications of tables and sketches of panel kits for 1 ɸ and 3 electric power system installation kits that can be used as physics practicum equipment and electrical machine installations at the Power Electronics Laboratory of the Mechanical Engineering Study Program of the South Aceh Polytechnic. The method used in the design of the electric power system installation kit is to collect design and fabrication data in accordance with the literature study on electricity based on the requirements and regulations of PUIL 2000, measure and calculate dimensions of the seat table and sketch diagram of electrical installation kits, do a drawing design as well as table fabrication and installation panel kits diagrams, determining the specifications of the tools and materials for the electric power system installation panel kits. From the results of the drawing and fabrication design, the dimensions for the installation kits table have a length of 1.50 m, a width of 1.30 m and a height of 0.90 m so that the volume of the table is 175.5 m3, and for the dimensions of the panel kits for the electric power system installation kits has a length of 1.40 m and a width. 1.20 m.